2014
DOI: 10.1002/fsn3.101
|View full text |Cite
|
Sign up to set email alerts
|

Solar drying and organoleptic characteristics of two tropical African fish species using improved low‐cost solar driers

Abstract: This study was done to evaluate the drying performance, efficiency, and effectiveness of five different types of improved low-cost solar driers in terms of moisture loss from two tropical African fish species Clarias gariepinus (African sharp tooth catfish) and Oreochromis niloticus (Nile tilapia) and testing the organoleptic characteristics of the dried samples. The driers used were made from plastic, aluminum, glass, glass with black igneous stone, and mosquito net, with traditional direct open-sun drying as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
1
9
0
1
Order By: Relevance
“…Sun drying in open space allows the settling of wind-borne dust, insect and bird infestation and increases inorganic content may be a probable reason for the increase in ash content (Immaculate et al, 2012). The higher ash content was due to the substantial loss of moisture (Mustapha et al, 2014). An increase in ash content was observed in kiln dried and electric oven dried catfish (Clarias gariepinus) from 3.06% to 3.92% and 3.62% (Chukwu and Saha, 2009).…”
Section: Changes In Proximate Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun drying in open space allows the settling of wind-borne dust, insect and bird infestation and increases inorganic content may be a probable reason for the increase in ash content (Immaculate et al, 2012). The higher ash content was due to the substantial loss of moisture (Mustapha et al, 2014). An increase in ash content was observed in kiln dried and electric oven dried catfish (Clarias gariepinus) from 3.06% to 3.92% and 3.62% (Chukwu and Saha, 2009).…”
Section: Changes In Proximate Compositionmentioning
confidence: 99%
“…High ambient temperature prevalent in tropics is responsible for faster spoilage and deterioration of tropical species. Hence quick preservation of fish is important which includes traditional methods like salting or brining, sun drying, solar drying, air drying and smoking in smoking kilns (Mustapha et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The overall quality of the dried mola fish was excellent as compared with the traditionally dried mola fish, where the color was brown and the texture was soft with off-odor. In general, Mustapha et al (2014) found that the physical parameters of open-sun dried fish was the least acceptable among the fish dried in five other solar driers. Abraha et al (2017) reported that the physical properties, such as color, flavor, appearance, texture and odor was superior for fish dried in a solar tent drier to fish dried in open-sun.…”
Section: Solar Fish Dryingmentioning
confidence: 96%
“…Using a natural convective solar drier, it was found that the drier was able to reduce the initial moisture content of bayad fish flakes from 78.67% to a final moisture content of 11.41% (Babiker et al, 2014). Mustapha et al (2014) studied five different solar driers and found that black stone-inserted glass drier showed the fastest drying rate in comparison to the plastic drier, mosquito net drier, glass drier and aluminum drier for drying African catfish and Nile tilapia. Martunis (2013) reported that the drying rate of fish using a force convection greenhouse was 3.29% per hour in a total drying time of 11 h while the same amount of fish took 2 days to dry in the sun.…”
Section: Solar Fish Dryingmentioning
confidence: 99%
“…Profil pengeringan tekwan pada ketiga rasio ikan dan tapioka menunjukkan adanya 2 periode laju penurunan. Profil pengeringan dengan 2 periode laju penurunan telah dilaporkan pada beberapa pangan segar seperti ikan (Reza et al, 2009;Mustapha et al, 2014), apel (Seiiedlou et al, 2010), dan rumput laut (Gupta et al, 2011).…”
Section: Analisis Dataunclassified